Telegram as a tool for journalists: Perception and use - Sánchez Gonzales, Hada M. (2020)
The search for alternative business models and the rise of new technologies have led to a transformation in the routines of journalists and the role of audiences. This debate has increased as a result of the prominence of platforms such as social networks or instant messaging applications. This study analyzes the implementation of Telegram in journalistic routines due to the usefulness, security and privacy offered by the platform. Thanks to these technical qualities, Telegram has broken into the routine practices of journalists, especially as a source of personalized information and as a news distribution channel. The perception of communication professionals and students is positive, in relation to the consumption of information through breaking news and relevant headlines due to the simplicity and originality of use of the application. However, in spite of its incursion into journalistic activity, its scarce social implantation still represents an important obstacle to its development at the level of the population.